(untitled) (Cardiovascular Journal, 2010)
Background: Radiofrequency (RF) catheter ablation is an effective method of treatment of patients with WPW syndrome. The purpose of this study was to analyze the initial and follow-up results of RF ablation of such cases in our hospital. Methods: 255 cases with WPW syndrome that had delta wave in sinus rhythm ECG underwent electrophysiological studies in this hospital. All the cases underwent radiofrequency ablation. These cases are selected for analysis. Results: Ablations were performed in these 255 patients between December 2005 and December 2008. One accessory pathway (AP) was found in 250 patients, two accessory pathways-in 05 patients. The mean duration of the procedure was 130 ± 32 min. The initial and overall success rate was 92.15% and 95.68% respectively. Major complications encountered are none. Conclusions: RF ablation of WPW syndrome has good initial (92.15%) and overall (95.68%) success rate and low recurrence rate (5.00%) at long term follow-up. Keywords: Catheter ablation; Radiofrequency ablation; WPW syndrome. DOI: 10.3329/cardio.v2i2.6638 Cardiovasc. j. 2010; 2(2) : 188-194